Comparison Study Between Enzymatic Hydrolysis & Acidolysis Lignins Isolated From Oil Palm Empty Fruit Bunch Pulps - H’ng, Yin Ying (2013)
Fundamental research on paper pulp produced from oil palm (Elaeis guineensis) empty fruit bunch (EFB) fiber was carried out in this study to gain better understanding of the residual lignin’s structures. Residual lignin was isolated from EFB chemical pulps which are kraft pulp, soda pulp, kraft-anthraquinone (AQ) pulp and soda-anthraquinone (AQ) pulp. In this study, there are two methods used for the isolation of residual lignin: acidic hydrolysis in dioxane-water 82:18 (v/v) with 0.1M hydrochloric acid (HCl) under reflux and enzymatic hydrolysis by using commercial cellulolytic enzymes in an acetate buffer with pH 4.5 at 45°C under continuous shaking. The time required for enzymatic hydrolysis procedure is much greater than the acidic hydrolysis procedure. Hence, in this experiment, the structures of residual lignin by these two methods are compared. Results showed that the enzymatic hydrolysis procedure gave lignin with higher yield than acidic hydrolysis did. Most of the enzymatic residual lignin could not dissolve in the common testing solvents such as tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), acetone, chloroform and so on whereas the acidolysis residual lignin able to dissolve easily in all the testing solvents. Fourier transform infrared spectroscopy (FTIR) absorption gave almost similar band for both isolated lignin such as OH stretch, CH stretch, S unit, G unit and so on. Besides that, carbon hydrogen nitrogen (CHN) elemental analysis showed higher percentage of nitrogen for the enzymatic residual lignin compared to the acidolysis residual lignin. UV spectroscopy showed that each isolated residual lignin contained different type of phenolic hydroxyl group. Proton nuclear magnetic resonance (ˡHNMR) showed limited signal and information for both isolated lignin due to low concentration. Furthermore, pyrolysis-gas chromatography mass spectrometry (PyGCMS) was carried out to examine the changes in the residual lignin.